Decoding Dictionaries: the Critical Perspective of Roksolana Zorivchak - Dzera, Oksana (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The article explores the critical legacy of Roksolana Zorivchak in Ukrainian lexicography. It argues that dictionaries function not merely as linguistic tools but also as essential instruments of cultural memory and national identity. This problem gains particular relevance in the context of globalization and Russian aggression, when issues of language, culture, and identity become especially acute. The aim of the article is to highlight Zorivchak’s role as a critic of Ukrainian lexicography and to assess the significance of her work for contemporary studies in metalexicography. The methodological foundation of the paper is based on the interdisciplinary approach encompassing Translation Studies, Metalexicography and Cultural Studies. The research combines historical and critical perspectives to trace the evolution of Ukrainian lexicography under varying sociopolitical conditions and applies methods of comparative analysis, discourse analysis and hermeneutic analysis. The main findings reveal that Prof. Zorivchak addressed a wide range of issues: from preserving national traditions in dictionary-making to introducing innovative approaches, especially in translation and terminological lexicography. Her critique exposes the manipulative potential of dictionaries in a totalitarian society while simultaneously emphasizing their role in restoring cultural continuity. Importantly, her legacy demonstrates how dictionaries can resist ideological pressure and serve as spaces for safeguarding linguistic diversity. Zorivchak’s observations continue to resonate in today’s scholarly debates, particularly in the context of decolonial approaches to Ukrainian studies. Thus, her contribution not only enriches Ukrainian lexicographic criticism but also provides a framework for understanding dictionaries as both scholarly and political instruments. The conclusions stress that revisiting Zorivchak’s contributions opens new avenues for studying dictionaries as instruments of cultural resistance, identity preservation, and integration of Ukrainian lexicography into the global academic landscape.